Survey of Marine Phytoplankton in Ship’s Ballast Tanks at Laem Chabang International Port, Thailand - Sumana Kajonwattanakul; Waranya Numnual; Thanyapas Sirichaiseth; Tanet Wannarangsri (Universitas Gadjah Mada, 2018)
Marine phytoplankton was investigated in ballast water of ships from 2010 to 2012 with a collection of 30 marine vessels that docked at Laem Chabang International Port in Chonburi Province, Thailand. The results showed that the dominant group of phytoplankton was diatoms. The amount of phytoplankton in the ballast tanks averaged less than 10 cells/ mL, which is less than Regulation D-2 of the Ballast Water Management Convention which requires that marine organisms between the sizes of 10 ? X <50 µm should be less than 10 cells/mL and size ? 50 µm should be less than 10 cell/m3 in ballast water. Alien species of phytoplankton was not recorded in this survey.